Isolation and characterization of lipogenesis inducing factor from Enkabang (Shorea macrophylla) - Beh, Chi Kin (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Enkabang nuts, foraged from Shorea macrophylla tree, are generally found in the Borneo Island, Jawa archipelago and in the Philippines. Enkabang nuts are highly rich in fat contents. It is inferred that an inducer of lipogenesis is found in the Enkabang nuts, which could then be applied to prediction of interaction between protein PPARγ and extracted compounds using molecular docking software. This research focused on extraction of Enkabang nut extracts by using Soxhlet extraction method and with solvents hexane, ethyl acetate and alcohol. Compound identification and overall profiling of Enkabang extracts were accomplished with Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Three major compounds in Enkabang were identified: methyl stearate; 9-octadecenoic acid, methyl ester, (E) and hexadecanoate <methyl->. In predictive molecular docking between protein PPARγ and extracted compounds using UCSF Chimera software and AutoDock Vina program, two compounds showed some potential as alternatives to induce lipogenesis pathway through PPARγ as predicted using the program. Compound pyrimidine-2,4,6(1H,3H,5H)-trione, 1-octadecyl- had bonded with amino acids SER289 and HIS323 of PPARγ, with binding affinity score of -6.5, while n-hexadecanoic acid had bonded with amino acids GLN286, SER289 and HIS323 with binding affinity score of -5.6. Further researches are required to identify and optimize the lipogenesis inducing factor extracted from Enkabang by exploring other proteins and lipogenesis pathways, and by optimizing the structures of extracted compounds in molecular studies.